Legal regulation of the President of Mongolia: some issues for improvement - Mendbayar, Dolgorsuren (Studia Philosophiae Et Juris, 2023)
In this academic article, we aim to compare the regulation of the rights of the President of Mongolia and international standards, and propose proposals for improving its legal environment. The institution of the President of Mongolia occupies a unique position in the system of our state power institutions, but first of all, it is noteworthy that the Constitution leaves it open as to which branch of the state power the institution of the President belongs to. According to the provisions of Article 3, Section 3.2 of the Law on the President of Mongolia, the President does not belong to any branch of state power. According to the amendments to the Constitution of 2019, Section 4 of the Thirty-third Article was changed to “The President may be granted certain mandates by law only within the scope specified in this Article.” It can be seen that this change has the content that specific powers of the President are only within the framework of the basic powers provided by the Constitution, and no new specific powers beyond the basic powers will be granted. Therefore, it is necessary to clarify the “other specific powers” of the President in the context of the basic powers stipulated in the Constitution, in order to comply with the content specified in Section 4 of the Thirty-third Article of the Constitution and to ensure the unity of the basic powers of the President.